Electric field-induced non-volatile 90° rotation of in-plane magnetic anisotropy in TbFeCo film grown on PMN-PT(0 1 1) substrate. (18th December 2019) - Xiao, Xia; Liu, Changqin; Wu, Yizheng; Chen, Haoran; Zhang, Dong; Liu, Ruxin; Yan, Xunling
Abstract: A TbFeCo alloy film with in-plane uniaxial magnetic anisotropy was fabricated by pulsed laser deposition on a (0 1 1)-oriented Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 (PMN-PT) substrate. By applying electric field along the surface normal, the magnetic easy axis was rotated 90° from the [0 1  ] to the [1 0 0] direction by strain-mediated magnetoelectric coupling. The modulation effect was further confirmed microscopically from variation of the magnetic domain configuration. Importantly, the magnetic easy axis remains along the [1 0 0] direction after removal of the electric field. We speculate that this non-volatile modulation was triggered by an irreversible rhombohedral to orthorhombic phase transition of PMN-PT.